2008
DOI: 10.1093/aje/kwm400
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Drinking, Cigarette Smoking, and Risk of Colorectal Adenomatous and Hyperplastic Polyps

Abstract: The authors evaluated alcohol drinking and cigarette smoking in relation to risk of colorectal polyps in a Nashville, Tennessee, colonoscopy-based case-control study. In 2003-2005, cases with adenomatous polyps only (n = 639), hyperplastic polyps only (n = 294), and both types of polyps (n = 235) were compared with 1,773 polyp-free controls. Unordered polytomous logistic regression was used to calculate adjusted odds ratios and 95% confidence intervals. Consumption of at least five alcoholic drinks per week wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 61 publications
8
101
1
2
Order By: Relevance
“…Risk factors for these include high intake of red meat and animal fat, low consumption of vegetables and fiber, sedentary life style, obesity and lower socioeconomic status. Alcohol consumption and smoking [30][31][32], use of aspirin and nonsteroidal anti-inflammatory drugs (NSAID) [33][34][35] and especially postmenopausal HRT use [15,19,20,[36][37][38][39][40] have also an important influence on CRC risk. Although we cannot fully evaluate the possible effects of all the mentioned risk factors for CRC, it seems unlikely that considerable changes in dietary and lifestyle habits oc- [22].…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for these include high intake of red meat and animal fat, low consumption of vegetables and fiber, sedentary life style, obesity and lower socioeconomic status. Alcohol consumption and smoking [30][31][32], use of aspirin and nonsteroidal anti-inflammatory drugs (NSAID) [33][34][35] and especially postmenopausal HRT use [15,19,20,[36][37][38][39][40] have also an important influence on CRC risk. Although we cannot fully evaluate the possible effects of all the mentioned risk factors for CRC, it seems unlikely that considerable changes in dietary and lifestyle habits oc- [22].…”
Section: Discussionmentioning
confidence: 99%
“…A Cohort study on 18,707 Korean adults after 11 years of follow-up showed that alcohol consumption was associated with an increased risk of CRC development among men. Also, the increase in duration and amount of alcohol consumption is directly related to the increase in CRC incidence (Shrubsole et al, 2008). The Health Professionals Follow-Up Study (HPFS) findings suggest that there is a positive relationship between alcohol consumption in men and CRC risk (Thygesen et al, 2008).…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…(1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). However, only a few studies using full colonoscopy to detect polyps have investigated the association between HP and smoking and between colorectal polyps and obesity or alcohol consumption (1,9,13,15,16). It is important to investigate the association between modifiable risk factors, such as obesity, smoking and alcohol and adenoma because most colorectal cancers arise from adenomas (17).…”
Section: Colorectal Polyps Are Classified Histologically As Adenomatomentioning
confidence: 99%
“…Chan et al (32) We found ten studies (1,5,7,10,12,13,16,29,33,34) regarding the association between ethanol consumption and colon polyps where all polyps were diagnosed by full colonoscopy. Three (1,13,16) of the ten studies also investigated the association between ethanol and HP. None of the three suggested a significant association.…”
Section: T a B L E 3 Ad J U S T E D Od D S Ra T I O S F O R Co L O mentioning
confidence: 99%